Study of Partnership Pattern Among Tilapia Fish (Oreochromis niloticus) Farmers with Fish Breeding Centre (BBI) Klemunan in Wlingi District, Blitar Regency. - Heri Ariadi; Zainal Abidin (Faculty of Fisheries and Marine Science, Brawijaya University, 2019)
Tilapia seeds is a fovorite of market commodities among fish farmers who are still not fully cultivated by fish farmers in Wlingi, Blitar Regency due to the limitations of market information. Based on this phenomenon, some farmers tried to establish a partnership system with the Breeding Fish Centre (BBI) Klemunan. The study purposed to analysis of the partnership pattern that occurs between tilapia seed farmers and BBI on effort to hatch and market tilapia fish using case studies qualitative approach. The results of the study show that based on the pattern and mechanism of cooperation carried out by both parties, it can be identified that the partnership pattern exists is a type of Firm-particular partnership. In Firm-particular partnership, BBI acts as a core partner have on obliged to provide technical assistance, while seed farmers act as plasma who are obliged present provide seed harvest to BBI for marketing. Relationship between the Firm-particular partnership is considered as a win-win solution that is beneficial positive impact for seed farmers to the procurement of superior fish, guaranteed to seed marketing, and obtaining knowledge of aquaculture technical. While for BBI Klemunan, this agreement might strengthen of brand image for the service assestment by costumer’s society.